(untitled) (CIPEEX, 2025)
Quality of Work Life (QWL) refers to the degree of employee satisfaction with various aspects of the work environment, including physical conditions, organizational climate, growth opportunities, rewards, and interpersonal relationships. For administrative staff, QWL directly influences their motivation, productivity, and overall well-being, as these professionals often deal with pressures, strict deadlines, and repetitive tasks. This study aimed to analyze the QWL of administrative staff at a University in the city of Ceres, Goiás. The research instrument used was the Walton QWL questionnaire, directed at 29 respondents and applied in person. The research results indicated that 87% of the staff rated the QWL as "excellent." This suggests that the majority of employees are satisfied with the working conditions provided by the institution, including factors such as compensation, security, and development opportunities. On the other hand, 13% of the respondents rated the QWL as "regular," which may indicate some areas of dissatisfaction or opportunities for improvement. Although most of the results were positive, the existence of a segment that does not consider the QWL to be excellent deserves the administration’s attention, as it may reflect the need for adjustments in specific aspects. In discussing the results, it is highlighted that the positive perception of QWL among most employees may be associated with effective people management policies adopted by the University, including investments in infrastructure, training, and a favorable organizational environment. However, the dissatisfaction of some employees suggests the need for a more in-depth analysis to identify specific points that may be negatively impacting the quality of work life. Continuous feedback programs, the creation of spaces for open dialogue, and initiatives aimed at employee well-being and mental health can be effective strategies to further improve QWL. It is concluded that, to ensure an even healthier and more satisfying work environment, it is essential for the institution to continue investing in continuous improvement policies, focusing on meeting the needs of all employees. Implementing strategies aimed at well-being can not only increase employee satisfaction and motivation but also promote a more harmonious and productive work environment.